Isolation and Characterization of Human Gut Bacteria Capable of Extracellular Electron Transport by Electrochemical Techniques - Naradasu, Divya; Miran, Waheed; Sakamoto, Mitsuo; Okamoto, Akihiro (Frontiers in Microbiology, 2019)
Microorganisms are known to exhibit extracellular electron transfer (EET) in a wide variety of habitats. However, as for the human microbiome which significantly impacts our health, the role and importance of EET has not been widely investigated. In this study, we enriched and isolated the EET-capable bacteria from human gut microbes using an electrochemical enrichment method and examined whether the isolates couple EET with anaerobic respiration or fermentation. Upon the use of energy-rich or minimum media (with acetate or lactate) for electrochemical enrichment with the human gut sample at an electrode potential of +0.4 V [vs. the standard hydrogen electrode (SHE)], both culture conditions showed significant current production. However, EET-capable pure strains were enriched specifically with minimum media, and subsequent incubation using the δ-MnO2-agar plate with lactate or acetate led to the isolation of two EET-capable microbial strains, Gut-S1 and Gut-S2, having 99% of 16S rRNA gene sequence identity with Enterococcus avium (E. avium) and Klebsiella pneumoniae (K. pneumoniae), respectively. While the enrichment involved anaerobic respiration with acetate and lactate, further electrochemistry with E. avium and K. pneumoniae revealed that the glucose fermentation was also coupled with EET. These results indicate that EET couples not only with anaerobic respiration as found in environmental bacteria, but also with fermentation in the human gut.